2015
DOI: 10.1016/j.pmrj.2015.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal Versus Oral Baclofen: A Matched Cohort Study of Spasticity, Pain, Sleep, Fatigue, and Quality of Life

Abstract: Background: Baclofen commonly is used to manage spasticity caused by central nervous system lesions or dysfunction. Although both intrathecal and oral delivery routes are possible, no study has directly compared clinical outcomes associated with these 2 routes of treatment. Objective: To compare spasticity levels, pain, sleep, fatigue, and quality of life between individuals receiving treatment with intrathecal versus oral baclofen. Design: Cross-sectional matched cohort survey study. Setting: Urban academic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 38 publications
1
35
1
1
Order By: Relevance
“…Previous studies have demonstrated dose stability by calculating the mean change in dose annually in years before the study [16,17]. The mean percent change in dose in the present cohort was not consistent with previous descriptions of minimal dose changes with long‐term use of ITB.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Previous studies have demonstrated dose stability by calculating the mean change in dose annually in years before the study [16,17]. The mean percent change in dose in the present cohort was not consistent with previous descriptions of minimal dose changes with long‐term use of ITB.…”
Section: Discussioncontrasting
confidence: 96%
“…The mean percent change in dose in the present cohort was not consistent with previous descriptions of minimal dose changes with long‐term use of ITB. One previous study reported mean percent changes in ITB doses of 3%, 3%, and 5% in 1 year, 2 years, and 3 years before time of study, respectively [17]; however, this previous study included a more heterogeneous population with a longer duration of therapy (mean 11 years) and was primarily composed of subjects with spasticity of spinal origin [17]. The mean percent dose changes in the present cohort were 7%, 13%, and 25% over the same period, suggesting of less dose stability in the acquired brain injury population.…”
Section: Discussionmentioning
confidence: 97%
“…4 In fact, McCormick et al showed that, although long-term use of intrathecal baclofen had a significant reduction in spasticity as compared to oral baclofen, there were no significant differences in pain, sleep, fatigue and quality of life. 8 Our study specifically analysed the average time spent for each patient to refill the baclofen pump in a hospital-based setting. We hope this study can fill the gap in the literature, as this information was not readily available during counselling for patients before the operation.…”
Section: Discussionmentioning
confidence: 99%
“…Any such off‐target effects would likely be held to the same standard of reaching some minimal clinically important difference regarding outcomes. Although targeted trials could be designed to quantify these off‐target effects, it is notoriously difficult to generate consistent data about many rehabilitation medicine outcomes, such as spasticity, within an often heterogeneous, small patient population [23,24]. For many of these difficult to objectively quantify realms, the intrinsic mechanisms contributing to their varied clinical presentations are likely insufficiently understood (at least to the degree needed to predict outcomes from the host of altered contributory neural signals).…”
Section: When the Research Participant Becomes A Co‐investigatormentioning
confidence: 99%